USING POINT-OF-CARE CARDIAC MARKERS IN LOW RISK CHEST PAIN IN THE EMERGENCY DEPARTMENT. Issue 5 (18th April 2015) - Griffiths, James; Humphrey, Julian; Pearson, Sally-Anne; Pallot, David
Abstract : Background: Barnsley Emergency Department, which recruited patients into the RATPAC trial, initiated a POC pathway for low-risk chest pain patients from December 2011. A preceding audit estimated that 50% of chest pain patients may be suitable for discharge from the ED. Methods: All patients who underwent POC testing for chest pain between December 2011 and July 2012 were identified from the Radiometer AQT™ database. Patient notes were then examined using Filestream™ data record system and time spent within the ED was assessed using Extramed™ patient tracking system. Results: A total of 1039 patients underwent POC testing during the period. Of these, 9 sets of notes were missing, giving a sample of 1030 patients. The age range was 16–96 (mean age 53.7 years) and 553 (54%) patients were male. Admissions: 649 patients were discharged from the ED (63%). However, when high risk patients and those admitted for other reasons (different diagnosis or social reasons), this percentage rises to 83% (649 discharges from 784 appropriate POC patients). Re-attendances: There were a total of 137 re-attendances within one month (13% of all patients). When unrelated attendances are removed, the number of significant re-attendances was 43 (4% of patients). Breaches: There were a total of 120 patients (11.6%) who breached the 4-hour access standard. During the 8-month period, there were a total of 2147 breaches and the average 4-hour performance for the trust was 95.65%. For the same period in the previous year, there were 2779 breaches and the average 4-hour performance was 94.27% Conclusion: Our pilot work would suggest that the use of POC cardiac markers in chest pain can facilitate discharge of low risk patients from the Emergency Department without a significant re-attendance rate or impacting on the 4-hour access standard.